2005
DOI: 10.1002/gea.20077
|View full text |Cite
|
Sign up to set email alerts
|

Experimental hearths and the thermal alteration of Caliche on the Southern High Plains

Abstract: Throughout the Holocene, caliche has been a ubiquitous technological resource for the people of the Southern High Plains. Archaeological sites on the Southern High Plains often contain thermal features that appear to utilize caliche nodules in various cultural processes. These processes usually involve some degree of thermal dynamic alteration to the caliche, identified in the archaeological record as fire-scorched or blackened nodules. Previous studies of the pyrodynamic properties of caliche have focused on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 19 publications
1
13
0
Order By: Relevance
“…With their high potential for preservation, attention is becoming more focused on these ubiquitous artifacts (Petraglia, 2002). Questions, therefore, regarding hearthstone use and performance characteristics have dominated the experimental literature (e.g., Backhouse et al, 2005;Brink and Dawe, 2003;Lintz, 1989;Pagoulatos, 2006). Despite this emphasis on examining hearthstone technology, relatively few studies have attempted to examine the thermal characteristics of hearthstones from a geologic perspective.…”
Section: Thermal Features Hearthstones and The Experimental Methodsmentioning
confidence: 97%
See 1 more Smart Citation
“…With their high potential for preservation, attention is becoming more focused on these ubiquitous artifacts (Petraglia, 2002). Questions, therefore, regarding hearthstone use and performance characteristics have dominated the experimental literature (e.g., Backhouse et al, 2005;Brink and Dawe, 2003;Lintz, 1989;Pagoulatos, 2006). Despite this emphasis on examining hearthstone technology, relatively few studies have attempted to examine the thermal characteristics of hearthstones from a geologic perspective.…”
Section: Thermal Features Hearthstones and The Experimental Methodsmentioning
confidence: 97%
“…The use of hearthstones in hot-rock technology has been well documented on the neighboring Southern High Plains (Backhouse et al, 2005;Johnson, 1987;Johnson and Holliday, 2004;Ladkin and O'Brien, 1995;Lintz, 1989). Investigations at PLK-Locality 4, a campsite near 41GR146, has resulted in the contextual identification of fractured Ogallala Fm.…”
Section: Introductionmentioning
confidence: 95%
“…What cook-stone features have in common, and thus what unites them under that rubric, is macroand microscopic evidencedwidely confirmed via middle range research (e.g., Backhouse et al, 2005;Brink and Dawe, 2003;Clabaugh, 2000;Gose, 2000;House and Smith, 1975;Jackson, 1998;Schalk and Meatte, 1988;Thoms, 1989)dthat the ostensibly oncehot rocks therein served as heating elements. That they were heated sufficiently, typically in excess of 500 C, is evidenced primarily by re-alignment of microscopic magnetic particles, enhanced oxidation that produced a ''reddened'' appearance, and micro-and macrofractures that yielded blocky and curvilinear fragments with sharp edges.…”
Section: Antiquity Of Hot-rock Cookerymentioning
confidence: 94%
“…In areas where stones were unobtainable, objects of baked clay were used for the same purpose''. Only within the last few decades, however, have archaeologists undertaken systematic studies of cook-stone features (e.g., Backhouse et al, 2005;Black and Creel, 1997;Brink and Dawe, 2003;Clabaugh and Thoms, 2007;Hodder and Barfield, 1991;Holdaway et al, 2005;House and Smith, 1975;Jackson, 1998;Latas, 1992;McParland, 1977;Petraglia, 2002;Pierce, 1984;Roll, 1982;Schalk and Meatte, 1988;Thoms, 1986). The extent to which studies pertaining to cook-stone technology have increased is revealed effectively by Doleman's (1996) well-circulated FCR bibliography as well as via a web-based search on ''fire-cracked rock.''…”
Section: Cook Stone As a Period Marker In North Americamentioning
confidence: 98%
“…Rocks can fracture, change colour and undergo other changes when exposed to heat (e.g., Backhouse et al, 2005;Domanski et al, 1994;House & Smith, 1975;Lintz, 1989;Mercieca, 2000;Purdy & Brooks, 1971;Schmidt et al, 2012). These changes are important for the identification of cooking with heated rocks (e.g., Ellwood et al, 2013;Thoms, 2009), but the people in the MSA do not appear to have used hot rocks when cooking (see e.g., Chapter 2).…”
Section: Fire-related Behaviourmentioning
confidence: 99%